Towards a Culture of Teaching-Cum-Research in Engineering Colleges: A Case Study of Rajarambapu Institute of Technology - Kulkarni, Sushma S.; Kamble, Vinay B. (Journal of Engineering Education Transformations, 2011)
Engineering has been a preferred option for students after the higher secondary level in India. As a result, the number of engineering colleges has seen a significant increase, especially in the private sector. And yet, the industries complain about a dire shortage of quality engineers. Initially, the setting up of IITs, RECs (later renamed as NITs) focussed on development of human resources in engineering and technology for our developing economy; and for sure, the Indian engineers have established their reputation in engineering and design skills. Today, we are competing globally not only in areas such as space, atomic energy, and agriculture, but also in conventional areas like automobiles, chemicals, pharmaceuticals and engineering equipment - crucial for social and economic development of the country. It is obvious that a critical issue for the future success of Indian industry is the growth of engineering education in India. This calls for development of a research culture in the engineering colleges and institutes of the country, and a policy to spread this culture effectively. It is emphasized that India's doctorate degrees are less than One per cent graduate engineering degrees. This percentage is much higher for most other developing and developed countries. Although, many engineering colleges / institutions are improving their research output, they are much below the norms attained by some of the best international institutions - more so in the case of the private colleges. There is no gainsaying the fact that the challenge for our engineering education system is to make a quick transition from primarily teaching institutions to teaching-cum-research institutions. We discuss in this paper, some of the mechanisms that would help transition in this direction, describing the efforts of Rajarambapu Institute of Technology, Islampur, as a case study.